Ethical considerations within pragmatic randomized controlled trials in dementia: Results from a literature survey - Stuart G. Nicholls; Kelly Carroll; Hayden P. Nix; Fan Li; Spencer Phillips Hey; Susan L. Mitchell; Charles Weijer; Monica Taljaard (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction This review aims to describe the landscape of pragmatic randomized controlled trials (RCTs) in the context of Alzheimer's disease (AD) and related dementias with respect to ethical considerations. Methods Searches of MEDLINE were performed from January 2014 until April 2019. Extracted information included: trial setting, interventions, data collection, study population, and ethical protections (including ethics approvals, capacity assessment, and informed consent). Results We identified 62 eligible reports. More than two‐thirds (69%) included caregivers or health‐care professionals as research participants. Fifty‐eight (94%) explicitly identified at least one vulnerable group. Two studies did not report ethics approval. Of 57 studies in which patients were participants, 55 (96%) reported that consent was obtained but in 37 studies (67%) no mention was made regarding assessment of the patients’ capacity to consent to research participation. Discussion Few studies reported protections implemented when vulnerable participants were included. Shortcomings remain when reporting consent approaches and capacity assessment.